Pengaruh Self Assessment System Terhadap Kepatuhan Pajak - Putri, Andiani; Adi, Priyo Hari (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
This study aims to determine how the tax compliance in the city of Kendal Regency. The variables used in this research are Self Assessment System, Equality Principle, and Tax Compliance. This study focuses on data on taxpayers in Kendal Regency. The data collection method used in this study is the method of distributing online questionnaires to 104 Civil Servants in Kendal Regency. Analysis of the data used is multiple linear regression analysis. Based on the research that has been done, it is proven that the self-assessment system has an effect on tax compliance while the principle of equality has no effect on tax compliance.Â Â